Kinetics of peripheral blood neutrophils in severe coronavirus disease 2019. Issue 4 (29th April 2021) - Metzemaekers, Mieke; Cambier, Seppe; Blanter, Marfa; Vandooren, Jennifer; de Carvalho, Ana Carolina; Malengier‐Devlies, Bert; Vanderbeke, Lore; Jacobs, Cato; Coenen, Sofie; Martens, Erik; Pörtner, Noëmie; Vanbrabant, Lotte; et al.
Abstract: Objectives: Emerging evidence of dysregulation of the myeloid cell compartment urges investigations on neutrophil characteristics in coronavirus disease 2019 (COVID‐19). We isolated neutrophils from the blood of COVID‐19 patients receiving general ward care and from patients hospitalised at intensive care units (ICUs) to explore the kinetics of circulating neutrophils and factors important for neutrophil migration and activation. Methods: Multicolour flow cytometry was exploited for the analysis of neutrophil differentiation and activation markers. Multiplex and ELISA technologies were used for the quantification of protease, protease inhibitor, chemokine and cytokine concentrations in plasma. Neutrophil polarisation responses were evaluated microscopically. Gelatinolytic and metalloproteinase activity in plasma was determined using a fluorogenic substrate. Co‐culturing healthy donor neutrophils with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) allowed us to investigate viral replication in neutrophils. Results: Upon ICU admission, patients displayed high plasma concentrations of granulocyte–colony‐stimulating factor (G‐CSF) and the chemokine CXCL8, accompanied by emergency myelopoiesis as illustrated by high levels of circulating CD10 −, immature neutrophils with reduced CXCR2 and C5aR expression. Neutrophil elastase and non‐metalloproteinase‐derived gelatinolytic activity were increased in plasma from ICU patients. Significantly higher levels of circulating tissue inhibitor of metalloproteinase 1 (TIMP‐1) in patients at ICU admission yielded decreased total MMP proteolytic activity in blood. COVID‐19 neutrophils were hyper‐responsive to CXCL8 and CXCL12 in shape change assays. Finally, SARS‐CoV‐2 failed to replicate inside human neutrophils. Conclusion: Our study provides detailed insights into the kinetics of neutrophil phenotype and function in severe COVID‐19 patients, and supports the concept of an increased neutrophil activation state in the circulation. Abstract : In this study, we found that patients suffering from severe COVID‐19 presented with immature, activated blood neutrophils and were characterized by elevated plasma levels of G‐CSF and CXCL8 that disappeared towards ICU discharge. Elevated neutrophil‐derived proteases in plasma of ICU patients were associated with increased non‐metalloproteinase‐derived gelatinolytic activity but decreased total MMP proteolytic activity. SARS‐CoV‐2 failed to replicate inside human neutrophils, suggesting that changes observed in neutrophils from patients with COVID‐19 are indirect consequences of SARS‐CoV‐2 infection in vivo .